Promoting Creative Competencies in Visual Arts for Middle School Students: Effective Strategies - Tog‘aev Keldiyor Xamidovich (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article examines effective strategies for promoting creative competencies in visual arts lessons for students in grades 5–7. The study focuses on enhancing students’ imagination, visual problem-solving skills, and artistic expression through interactive teaching, collaborative activities, and the use of diverse materials. Practical recommendations are provided for implementing these strategies in classrooms to foster creativity and engagement, supporting both cognitive and personal development.